PENINGKATAN PRESTASI BELAJAR SISWA MELALUI PENGGUNAAN METODE PEMBELAJARAN GROUP INVESTIGATION - Muhammad Fajar Maulana; Pargito Pargito; Darsono Darsono (Jurnal Studi Sosial / Journal of Social Studies, 2014)
This research dilatar like problem the low study result. Research the act of this class aims to improve performance studied history.Learning method applied is learning cooperative type group investigations. The results showed that success indicator learning method Group Investigation on cycle I have not succeeded because of the many students who get average value of 56,35 while the new students achieve learning exhaustiveness 32,43% (minimum requirement is said to be successful) (75%). in cycle II has not been successful because of the many students who get average grades 65,13 while new students achieve learning ketuntasan 59,46% (minimum requirement is said to be successful) (75%). in cycle III succeeds because of the many students who get average value of 67,43 while the exhaustiveness student learning has reached 75,67% already eligible students can study a minimum exhaustiveness (75%).Penelitian ini dilatar belakangi masalah rendahnya hasil belajar siswa. Penelitian tindakan kelas ini bertujuan untuk meningkatkan prestasi belajar Sejarah. Metode pembelajaran yang diterapkan yaitu pembelajaran kooperatif tipe Group Investigations. Hasil Penelitian menunjukkan bahwa indikator keberhasilan pembelajaran metode Group Investigation pada siklus I belum berhasil karena banyaknya siswa yang mendapat nilai rata-rata 56,35 sedangkan ketuntasan belajar siswa baru mencapai 32,43% (syarat minimal dikatakan berhasil) (75%). pada siklus II belum berhasil karena banyaknya siswa yang mendapat nilai rata-rata 65,13 sedangkan ketuntasan belajar siswa baru mencapai 59,46% (syarat minimal dikatakan berhasil) (75%).pada siklus III berhasil karena banyaknya siswa yang mendapat nilai rata-rata 67,43 sedangkan ketuntasan belajar siswa sudah mencapai 75,67% sudah memenuhi syarat ketuntusan minimal belajar siswa (75%).Kata kunci: group investigations, kooperatif, prestasi belajar